Zebra mussel beds: an effective feeding ground for Ponto-Caspian gobies or suitable shelter for their prey? - Kobak, Jarosław; Poznańska, Małgorzata; Jermacz, Łukasz; Kakareko, Tomasz; Prądzynski, Daniel; Łodygowska, Małgorzata; Montowska, Karolina; Bącela-Spychalska, Karolina (PeerJ (San Francisco, CA), 2016)
Aggregations of the Ponto-Caspian invasive zebra mussel ( Dreissena polymorpha ) constitute a suitable habitat for macroinvertebrates, considerably increasing their abundance and providing effective antipredator protection. Thus, the overall effect of a mussel bed on particular predator species may vary from positive to negative, depending on both prey density increase and predator ability to prey in a structurally complex habitat. Alien Ponto-Caspian goby fish are likely to be facilitated when introduced into new areas by zebra mussels, provided that they are capable of utilizing mussel beds as habitat and feeding grounds. We ran laboratory experiments to find which prey (chironomid larvae) densities (from ca. 500 to 2,000 individuals m −2 ) in a mussel bed make it a more beneficial feeding ground for the racer goby Babka gymnotrachelus (RG) and western tubenose goby Proterorhinus semilunaris (WTG) compared to sandy and stone substrata (containing the basic prey density of 500 ind. m −2 ). Moreover, we checked how food availability affects habitat selection by fish. Mussel beds became more suitable for fish than alternative mineral substrata when food abundance was at least two times higher (1,000 vs. 500 ind. m −2 ), regardless of fish size and species. WTG was associated with mussel beds regardless of its size and prey density, whereas RG switched to this habitat when it became a better feeding ground than alternative substrata. Larger RG exhibited a stronger affinity for mussels than small individuals. WTG fed more efficiently from a mussel bed at high food abundances than RG. A literature review has shown that increasing chironomid density, which in our study was sufficient to make a mussel habitat an attractive feeding ground for the gobies, is commonly observed in mussel beds in the field. Therefore, we conclude that zebra mussels may positively affect the alien goby species and are likely to facilitate their establishment in novel areas, contributing to an invasional meltdown in the Ponto-Caspian invasive community.